Potentials of artificial intelligence (AI) in collection development in university libraries - Omeluzor, Saturday U.; Ojukwu, Njideka Nwawih Charlotte (Communicate: Journal of Library and Information Science, 2025)
The purpose of this study was to identify the potentials of Artificial Intelligence (AI) on collection development in the university library in Nigeria. The study used the research survey method and descriptive research analysis. The instrument for data collection was a structured questionnaire. The population of the study comprised a total of 574 librarians in Nigeria who attended the 2024 NLA conference/Annual General Meeting (AGM) that held at the University of Port Harcourt from 7th to 12th July, 2024. The result showed that AI technology has the potentials of effective prediction, automation, analysis, elimination of repetitive tasks, forecasting, budgeting and reviewing of collection development at the university library. The result further revealed that AI can reduce time and resource wastage in collection development thereby boosting library collection with ease. The adoption of AI would enhance the collection development unit while improving the overall services of the university library. The research recommended the adoption of AI for collection development unit to enhance the services in the unit.